You can put this solution on YOUR website!
Because the leading exponent is even and the leading cofficient is negative we know that as x goes to -infinity f(x) goes to -infinity and as x goes to positive infinity f(x) goes to -infinity.
plug in a few negative values for x and a few positive values for x and solve for f(x), which is y.
f(-2)=-(-2)^4+2=-16+2=-14 Plot (-2,-14)
f(-1)=-(-1)^4+2=-1+2=1 Plot (-1,1)
f(0)=-(0)^4+2=0+2=2 Plot (0,2)
f(1)=-(1)^4+2=-1+2=1 Plot (1,1)
f(2)=-(2)^4+2=-16+2=-14 Plot (2,-14)
Connect the dots and you have a graph.
If you're taking calculus let me know because there are other things you can do.